Proofreader’s Figure in Plot and Meta-Plot of the Novel “Transparent Things” by V. V. Nabokov - E. G. Nikolayeva (Научный диалог, 2019)
The article analyzes the functions of “proofreading” in the structure of the plot and meta-plot of the novel “Transparent Things” by V. V. Nabokov. The image of proofreader Hugh Person is considered in two paradigms: “hero-proofreader - hero-writer” and “proofreader as an assistant to the author - author-creator.” The main part of the study is dedicated to track the dynamics of the hero: his movement from “deafness” to the author’s voice (errors in the proof) to understanding the “service” function of a corrector (the hero as “the employee”) and plan of the Creator. The paper focuses on the multilinguistic game and distinguishes the signs of the author’s presence in the novel’s text. In conclusion, the article draws conclusions about the meta-literary potential of the hero-proofreader in the plot, as well as the ambiguity of his figure in the poetics of this author. In addition, the function of heroes’ clothes is considered. The extent and quality of connectedness of the characters with objective reality are interpreted as a signal of the hero’s execution / non-execution of his function in the novel. Also in the work the interpretation of the hotel locus as a temporary “refuge” of the hero in the space of the text is given. A special emphasis is made on the glass showcase as a way to demonstrate the Author’s techniques and planned plot moves. proofreader